CARTOGRAPHY AS A POSSIBLE PATH WHEN RESEARCHING MATHEMATICS EDUCATION Some research by Coletivo Cronopies+ - Bernal, Jorge Isidro Orjuela [UNESP]; da Solidade Santos, Heinrich [UNESP]; Lopes, Wanderson Rocha [UNESP]; Lopes, Ronilce Maira Garcia; Suarez, Jeimy Marcela Cortes [UNESP] (Universidade Federal de Sao Paulo, 2024)
The following proposal explores and discusses the potential of Cartography as a methodological path in the development of research in Mathematics Education aimed at working with different groups that, in many cases, in addition to finding themselves in various situations of vulnerability and social neglect – taken in their potentiality of life –, are not necessarily linked to formal or informal academic training spaces, such as schools or universities. To this end, we begin with a general presentation of the doctoral research carried out by five members of the research group Coletivo Cronopies+ (cronopiando.org) and, in addition, we invite the participants of the session to visit the first Hip Hop House in Brazil in Diadema/SP, which constitutes one of the settings that make up the fieldwork of one of the research projects presented. The research we share involves working with a Hip Hop cultural center in Piracicaba/São Paulo (SP), a Guarani-Kaiowá indigenous village in Coronel Sapucaia/Mato Grosso do Sul (MS), a traveling school in a Landless Workers’ Movement camp in Porecatu/Paraná (PR), a rural settlement school in Nova União/Rondônia (RO) and three collectives that operate with gender in the region of Rio Claro/SP. The construction of this proposal is methodologically based on Cartography, since the discussion aims to produce the field of this research and we propose “fieldwork”.
LA CARTOGRAFÍA COMO CAMINO POSIBLE EN LA INVESTIGACIÓN EN EDUCACIÓN MATEMÁTICA Algunas investigaciones del Coletivo Cronopies+
A CARTOGRAFIA COMO UM CAMINHO POSSÍVEL AO PESQUISAR NA EDUCAÇÃO MATEMÁTICA ALGUMAS PESQUISAS DO COLETIVO CRONOPIES+
Keywords: cartography; collective; diversity; mathematics education; philosophy of difference